The role of financial inclusion in driving women's economic empowerment. Issue 8 (17th November 2019) - Hendriks, Sarah
ABSTRACT: This article highlights why the Bill & Melinda Gates Foundation has focused on financial inclusion to advance women's economic empowerment and drive progress on gender equality. It highlights key lessons from financial inclusion-related projects the foundation has supported within the "Putting Women and Girls at the Center of Development (WGCD) Grand Challenge" in 2015. The article also shares the logic and research informing the foundation's strategy to close the gender gap in financial inclusion – a key pillar of its strategy on women's economic empowerment – and improve the lives and livelihoods of millions of women around the world.